Leveraging Cloud Computing and Machine Learning for Claims Management Optimization and Customer Satisfaction: A Study of Insurance Companies in Lagos State - Perpetua, Ehiogu Chizoba; Omorodion, Stanley (Research Parks Publishers, 2025)
This study analyzed the influence of cloud computing and machine learning on claims management optimization and customer satisfaction in Lagos State insurance businesses, adopting a survey research methodology and collecting data from respondents in selected insurance companies in Lagos State, Nigeria. The data found that cloud computing had a considerable favorable influence on claims handling, whereas machine learning had no meaningful effect on customer satisfaction. The research underlined the need for insurance firms to utilize cloud computing technologies to enhance their claims management operations and to re-evaluate their machine learning methods to boost client satisfaction. The research ended by advising that insurance firms embrace cloud computing to better claims administration efficiency and create efficient machine learning tactics to improve client satisfaction.